Markerless augmented reality on ubiquitous mobile devices with integrated sensors - Van Wyk, Carel (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.